ANALISIS WACANA KRITIS MENGGUNAKAN TEORI THEO VAN LEUWEEN PADA BERITA ONLINE “GAJI HONORER TAK DI BAYAR, KEPSEK DI MARGO TABIR JADI TERSANGKA” - Monica, Juwita Serli; Alhadjrath, Elza Rahila Alhadjrath; Saputra, Ade Bayu (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Jambi, 2023)
Critical Discourse Analysis is a method that can be used to analyze both spoken and written discourse. In critical discourse analysis, not only the language aspect is studied but also the context that accompanies it. This study aims to look at the different points of view from various online media including Tribun Jambi.com, kuatbaca.com, PikiranRakyat.com, and Kompas.com in constructing the case of a 12-year-old child running away from an Islamic boarding school and being fined 37 million. The discourse analysis model used is Theo Van Leuween’s model with the aim of detecting and researching how parties are marginalized in a discourse. The data for this research were obtained from online media coverage in the period 5-12 November 2022. The method used in this research is descriptive qualitative. . Van Leeuwen’s analysis in general shows how parties and actors (can be a person or group) are presented in the news. Differences in writing in various online media give rise to various perceptions from readers. Keywords: critical discourse, Theo Van Leuween, online media